Технології і інформаційно-комунікаційні системи - Шеховцов, А. В.; Козел, В. М. (Eastern-European Journal of Enterprise Technologies, 2009)
General description of the large-scale of informatively-communication systems is given (IСS). The algorithms of analysis and functioning of morphological models are resulted IСS for the automated system «Vybory», and also results of his classification of integral indexes